ANALISIS PENGARUH KETERLIBATAN ORANG TUA DALAM PROSES PEMBELAJARAN TERHADAP PRESTASI BELAJAR SISWA SD - Farida Salsabila; Henry Aditia Rigianti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Parental involvement is an important part of the student learning process. The aim of this research is to determine the effect of parental involvement in the learning process on student learning achievement which will be carried out at SD N Krapyak Wetan. Descriptive qualitative research was used in research planning. The research results show that parental involvement can influence student achievement in the learning process. The role of parents in accompanying learning at home has a good impact on the learning environment for students and their families. Students' enthusiasm for studying at school increases with their proficiency in the material they have studied at home.